The Strategic Use of Blockchain and Information Technology in Financial Inclusion and Sectors - El-Begawi, Mona Khalil (AUC Knowledge Fountain, 2019)
Information Technology, and more specifically Blockchain, has taken over many industries, changing their fundamentals in order to increase productivity and efficiency. The world is now moving into the Fourth Industrial Revolution, which merges the tangible and intangible world in ways previously not known to man, such as biotechnology and other disruptive technologies. Changes happening nowadays have affected the requirements for labor and their productivity, profitability of data in general, and the strategic use of Blockchain and Information Technology (IT); meanwhile, there are fears that occur from simple changes. This paper aims to understand the literature revolving the strategic use of Blockchain and IT in the realm of economics - more specifically financial inclusion and institutions, with the possible extensions it poses. It has also examined Egypt's situation in terms of financial inclusion and institutions within the jurisdiction of mobile phone penetration and usage of internet. All this then boils down into a brief policy recommendatio